The great divergence: A network approach - Ines Lindner; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
We present a multi-country theory of economic growth in which countries are connected by a network of mutual knowledge exchange. Growth is generated through human capital accumulation and knowledge externalities. The available knowledge in any country depends on its connections to the rest of the world and on the human capital of the countries it is exchanging knowledge with. We show how the diffusion of knowledge through the world explains the evolution of global income inequality. It generates a Great Divergence, that is increasing world inequality after the take-off of the forerunners of the industrial revolution, followed by a Great Convergence, that is decreasing world inequality after the take-off of the latecomers of the industrial revolution. Knowledge diffusion through a Small World network produces an extraordinary diversity of individual growth experiences of initially identical countries including differentiated take-offs to growth as well as overtaking and falling behind in the course of world development.
Keywords: O10; O40; D62; D85; F41; 330; networks; knowledge diffusion; economic growth; world income distribution